2007
DOI: 10.1111/j.1439-0418.2007.01171.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of transgenic maize hybrids to variant western corn rootworm larval injury

Abstract: In 2005 and 2006, transgenic insecticidal maize hybrids (YieldGard Rootworm, MON 863, Cry3Bb1, Vector ZMIR 13L) were evaluated for their ability to limit root injury caused by western corn rootworm (Diabrotica virgifera virgifera LeConte) larval feeding. Hybrids in each year of the experiment were planted in plots that had been devoted to a trap crop (late-planted maize interplanted with pumpkins) the previous growing season. All maize hybrids were provided by Monsanto Company and the genetic backgrounds remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…Under higher levels of rootworm abundance, where the untreated control displayed injury of 1.5 nodes to greater than two nodes of injury, Cry3Bb1 maize always had less than 0.75 nodes of root injury (Ma et al, 2009). In a large-scale study conducted by Gray et al (2007), eight commercialized hybrids were evaluated in three separate studies. In each study, injury to the experimental control of non-Bt maize was at least 2.0 nodes and as high as 2.74 nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Under higher levels of rootworm abundance, where the untreated control displayed injury of 1.5 nodes to greater than two nodes of injury, Cry3Bb1 maize always had less than 0.75 nodes of root injury (Ma et al, 2009). In a large-scale study conducted by Gray et al (2007), eight commercialized hybrids were evaluated in three separate studies. In each study, injury to the experimental control of non-Bt maize was at least 2.0 nodes and as high as 2.74 nodes.…”
Section: Discussionmentioning
confidence: 99%
“…This level of injury is higher than other published accounts of injury for commercialized Cry3Bb1 maize hybrids. [55][56][57] Averaging across several studies, Dun et al 58 found a 17.9% reduction in yield for each node of roots lost to feeding by western corn rootworm, indicating that in seven of the fields visited in 2010 farmers may suffer substantial reductions in yield.…”
Section: Discussionmentioning
confidence: 99%
“…Higher damage was particularly found in roots dug in early August compared with roots dug 3 wk earlier in midJuly, a more traditional time to evaluate corn rootworm damage (Gray and Steffey 2005). Gray et al (2007) reported that the average damage rating (Oleson et al 2005) of the eight commercial YieldGard Rootworm hybrids increased from an average rating of 0.17 on 24 July to 0.40 on 8 August 2006 in Monmouth, Mention of trade names or commercial products in this publication is solely for the purpose of providing speciÞc information and does not imply recommendation or endorsement by the U.S. Department of Agriculture. IL, and from 0.31 on 20 July to 0.80 on 7 August 2006 in Urbana, IL.…”
mentioning
confidence: 97%